PENGARUH PENGGUNAAN MEDIA INTERAKTIF DISERTAI PENGISIAN TTS TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS XI DI SMAN 2 LENGAYANG KABUPATEN PESISIR SELATAN - Pramanda Elva, Widia; nerita, siska; Susanti, Diana (STKIP PGRI Sumbar, 2014)
ABSTRACT In the learning process the teacher as the facilitator should be able to use the varyingstrategies and media, so that stud ents learn more in the spirit and learning process more interesting,so that student learning outcomes for the better, because of the low student learning outcomes arecaused b y many factors, both factors of students and factor of the teacher. Therefore, teachers canuse a variety of strategies and media are varied, so that the goal can be achieved with goodlearning. One of them is the use o f interactive media with charging TTS, This study aims todetermine the effect of the use of interactive med ia with charging TTS on learning outcomes inbiology class XI student of SMAN 2 Lengayang, This research is an experimental study with adesign Rando mized Control Group Posttest Only Design. The population in this study were allstudents of class XI in SMAN 2 Lengayang enrolled in the second semester of academic year200 13 /2014. Sampling was done by p urposive sampling technique. Then by using purposivesampling obtained experimental class ( XIIA1 ) and control classes ( XIIA2 ). Data were analyzedusing t-test. Fro m the results of the study revealed that the experimental class had an average value( 74,91 ) is higher than the average value of the control class ( 59,8 ). After the data were analyzedby t test, obtained the price thi t ung 7, 16 and tt ab e l 1, 67. Thus t c oun t > t t a bl e , which means that H1 isaccepted. In other words, it can be concluded that the use of interactive media with charging TTShas an influence on learning outcomes in biology class XI student of SMAN 2 Lengayang.